Prevalence, antibiogram, and multidrug-resistant profile of E. coli O157: H7 in retail raw beef in Addis Ababa, Ethiopia - Haile, A.F.; Alonso, Silvia; Belay, N.; Atoma, T.B.; Boyaka, P.N.; Grace, Delia (Frontiers Media, 2022)
Escherichia coli O157:H7 is an emerging foodborne pathogen of public health importance. The objectives of this study were to estimate the prevalence and evaluate the antimicrobial susceptibility pattern and multidrug-resistant profile of E. coli O157:H7 isolated from raw beef sold in butcher shops in Addis Ababa, Ethiopia. A total of 384 raw beef samples were collected from randomly selected butcher shops across the 10 sub-cities of Addis Ababa. E. coli O157:H7 was isolated following ISO-16654:2001 standard, and isolates were tested for resistance to 13 antimicrobial agents using the Kirby–Bauer disk diffusion method. Out of the 384 retail raw beef samples examined, 14 (3.64%) (95% CI = 1.77–5.51%) carried E. coli O157:H7 serotype. Of the 14 E. coli O157:H7 isolates, 8 (57.14%) were found to be resistant to three or more antimicrobial categories. The frequency of resistant phenotype was more common for ampicillin (92.8%), nitrofurantoin (92.8%), and tetracycline (50%). Multidrug-resistant E. coli O157:H7 were present in raw beef sold in butcher shops in Addis Ababa. Thus, more stringent monitoring of antimicrobial use in both human and animal populations should be implemented. In addition, further studies should be conducted to understand the E. coli O157:H7 points of contamination and define appropriate risk mitigation strategies.